2014
DOI: 10.1098/rsta.2014.0116
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus cloud seeding: a climate engineering mechanism with reduced side effects?

Abstract: Climate engineering, the intentional alteration of Earth's climate, is a multifaceted and controversial topic. Numerous climate engineering mechanisms (CEMs) have been proposed, and the efficacies and potential undesired consequences of some of them have been studied in the safe environments of numerical models. Here, we present a global modelling study of a so far understudied CEM, namely the seeding of cirrus clouds to reduce their lifetimes in the upper troposphere, and hence their greenhouse effect. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In a simulation using a coupled atmosphere‐ocean general circulation model (GCM), CCT cooled Earth's climate by 1.4°C [ Storelvmo et al ., ]. Climate model simulations of the climate response to CCT, in which CCT was approximated by an increase in ice particle fall speed (fall speed was doubled by Muri et al [] and quadrupled by Crook et al []), yielded reductions in CRF and cooling of global annual mean temperature (−0.94°C and −1.0°C, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a simulation using a coupled atmosphere‐ocean general circulation model (GCM), CCT cooled Earth's climate by 1.4°C [ Storelvmo et al ., ]. Climate model simulations of the climate response to CCT, in which CCT was approximated by an increase in ice particle fall speed (fall speed was doubled by Muri et al [] and quadrupled by Crook et al []), yielded reductions in CRF and cooling of global annual mean temperature (−0.94°C and −1.0°C, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Bala et al [], Tilmes et al [], and Niemeier et al [] all found that the reduction in net SW radiation flux at Earth's surface from SRM was associated with reduced surface evaporation and weakening of the hydrological cycle. In simulations of CCT, however, global mean precipitation changes were small [ Muri et al ., ] or involved relatively small reductions [ Storelvmo et al ., ]. In a comparison of CCT and SRM methods using the same climate model and identical simulation design, Crook et al [] found that CCT increased global precipitation in contrast to decreases found for all of the SRM methods tested.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Storelvmo et al (2013Storelvmo et al ( , 2014 have quantified the direct radiative effects produced by seeding uppertropospheric cirrus ice clouds with large IN. Although this is not directly related to our specific discussion on SG side effects, it can be considered as indirect evidence of the importance of correctly understanding the balance between the complex microphysical processes regulating the formation and growth of upper-tropospheric ice particles.…”
Section: Ice Formation Via Heterogeneous Freezingmentioning
confidence: 99%
“…The spatially non-homogeneous forcing induces circulation changes with the risk of side effects in remote unseeded regions [65,66]. Another study found that the cooling resulting from seeding of mid-and high-latitude cirrus is accompanied by only a modest reduction in rainfall [67]. Combining Bthinning^of cirrus with projected CO 2 increases in multidecadal climate simulations led to an enhancement of the hydrological cycle [68].…”
Section: Geoengineering Of Cirrusmentioning
confidence: 99%